Metabolomic Study of Heterotrophically Grown Chlorella sp. Isolated from Wastewater in Northern Sweden - Jean Claude Nzayisenga; Anita Sellstedt (Molecules, 2021)
There are numerous strains of Chlorella with a corresponding variety of metabolic pathways. A strain we previously isolated from wastewater in northern Sweden can grow heterotrophically as well as autotrophically in light and has higher lipid contents under heterotrophic growth conditions. The aims of the present study were to characterize metabolic changes associated with the higher lipid contents in order to enhance our understanding of lipid production in microalgae and potentially identify new compounds with utility in sustainable development. Inter alia, the amino acids glutamine and lysine were 7-fold more abundant under heterotrophic conditions, the key metabolic intermediate alpha-ketoglutarate was more abundant under heterotrophic conditions with glucose, and maltose was more abundant under heterotrophic conditions with glycerol than under autotrophic conditions. The metabolite 3-hydroxy-butyric acid, the direct precursor of the biodegradable plastic PHB (poly-3-hydroxy-butyric acid), was also more abundant under heterotrophic conditions. Our metabolomic analysis has provided new insights into the alga’s lipid production pathways and identified metabolites with potential use in sustainable development, such as the production of renewable, biodegradable plastics, cosmetics, and nutraceuticals, with reduced pollution and improvements in both ecological and human health.